Knowledge, Skills and Self-Confidence in Basic Life Support and Automated External Defibrillator (AED) using among under Graduated Nursing Students - Ruangrit, Rattikarn; Keawpimon, Preeya; Sengloiluean, Kittiphong (Princess of Naradhiwas University Journal, 2021)
This research is descriptive research aimed at studying the knowledge, skills, and self-confidence in Basic Life Support (BLS) and the use of Automated External Defibrillator (AED) of undergraduate nursing students studying in junior year. 35 participants in the research received BLS and AED training. The tools used to collect data were BLS and AED knowledge and skill tests and a chest compression performance test on a Brayden pro with real-time feedback, which the data were analyzed by descriptive statistics and content analysis. The results revealed that almost all of the participants were female (85.71%) with the average age of 20.94 years (S.D.=0.59). They had received BLS training ( =3.94, S.D.=1.14) and the AED training ( =2.57, S.D.=1.12) but never applied in a real life situation. Their level of self-confidence of BLS and the use of AED were at a moderate level ( =5.69, S.D.=1.02 and =6.31, S.D.=1.30), respectively. Level of knowledge was between a good (42.86%) and an excellence level (25.71%). Level of BLS skill was between a good level (31.43%) and an excellence level (42.86%). Level of the use of AED skill was between a good (54.29%) and an excellence level (34.29%). The performance of chest compression as recommended by the 2015 American Heart Association Guidelines had not reached the standard in the areas of shallow and specified rate of compression, hand placement, full chest recoil and time per one circle. In conclusion, BLS and AED training programs should be initially established in various simulated case scenarios. The programs should be taught by certified BLS instructors and real-time feedback should be provided at training sessions in order to reflect learners’ performance. It could help them to improve their self-confidence.